Cicero and his Clamorous Silences: was he Fair Enough with the Epicure-ans and their Ethical and Political Views? - Javier Aoiz, JA; Marcelo D. Boeri, MDB (Ciceroniana On Line)
If our knowledge of Epicurean philosophy depended exclusively upon the information conveyed by their adversaries, we would be practically unaware of the political component of the Epicurean study of nature (φυσιολογία), and of the political considerations that grounded the Epicurean way of life. This paper shows how Cicero omits some elements of Epicureanism that are crucial to understanding how political reflection was integrated into Epicurean philosophy. We argue that Cicero consciously omits important details of Epicurean arguments regarding ethics and politics and includes some silences that can be described as «clamorous». By bypassing the crucial interconnection between political theory and the Epicurean study of nature, Cicero includes passing reference to Epicurean contractualism and he does not set out the Epicurean theoretical framework in which it was originally inscribed.